OpenedEyes: A web standards-based generic framework for multidimensional information visualization - Almeida, Caio Sacramento de Britto; Apolinário Jr., Antônio Lopes (Journal on Interactive Systems, 2013)
A huge amount of digital data is produced everyday, which led us to a situation called ”data pollution”. A big challenge is to extract knowledge from all this data, but many times it is presented in a way that is not friendly for a human being. Information visualization tries to solve this problem by representing datasets graphically and so making easier the task of comprehending a large dataset. Many of the available information visualization tools focus on desktop, require advanced skills from the user or are based on proprietary technologies. This work proposes an open source framework for information visualization called OPENEDEYES, written in pure JavaScript and based on web standards. The framework implements some interactive visualization tools that run on any modern web browser, which shows its flexibility and extensibility. A case study using a real dataset was made for an empirical framework evaluation. Finally, a new visualization technique was proposed, a variation of the classic parallel coordinates technique, optimized for the web environment and for large datasets.